Surgery for spinal tuberculosis: a multi-center experience of 582 cases - Alam, Md. Shah; Phan, Kevin; Karim, Rezaul; Jonayed, Sharif Ahmed; Munir, Hasan Khalid Md.; Chakraborty, Shubhendu; Alam, Tashfique (Journal of Spine Surgery; Vol 1, No 1 (December 21, 2015): Journal of Spine Surgery, 2015)
Background: Tuberculosis (TB) of the spine is a common site of osseous TB, accounting for 50%-60% of cases. Spinal TB still occurs in both developed and developing countries. The diagnosis of spinal TB is difficult and it commonly presents at an advanced stage. Delays in establishing diagnosis and management result in complications such as spinal cord compression and spinal deformity. Methods: A total of 582 patients with TB of the cervical, thoracic and lumbar spine with moderate to severe cord compression were studied. Variable degrees of neurological deficit with deformity were treated from January, 2003 to July, 2014. Thoracotomy along with anterolateral decompression and autogenous strut bone grafting with simultaneous fixation by screws and rods were performed in 113 cases. Posterior decompression, posterior interbody and posterolateral fusion by bone graft with stabilization by transpedicular screws and rods were done in the remaining 469 cases. Appropriate anti-TB drugs were given to all patients for 18-24 months. The follow-up period was 3 months to 10 years. Results: The average age was 32.5 years. All patients survived surgery. There were 7 cases of superficial infections (1.2%) whilst there were 4 cases (0.7%) of deep infections. Revision surgery was performed in 6 patients (1.0%). Implant failure occurred in 4 cases (0.7%) whilst malposition of screws occurred in 12 cases (2.1%). Perioperative bleeding complications were reported for 4 patients (0.7%). Neurological improvement occurred in all patients except for 2 cases (0.3%). Preoperatively, the majority of patients (n=221, 38%) were classified with Class A on the American Spinal Injury Association (ASIS) neurological impairment scale. This was significantly reduced postoperatively to 0.4%. Conclusions: For patients with spinal TB anterior debridement, auto graft bone fusion, anterior or posterior fixation appears to be effective in arresting disease, correcting kyphotic deformity and maintaining correction until solid spinal fusion.